Studi Etnoekologi tentang Nelayan dan Jaring Cantrang di Kabupaten Rembang - Hesti Rofika Sari; Nugroho Trisnu Brata (JSW (Jurnal Sosiologi Walisongo), 2017)
The article discuss about ecology among fisherman community who use cantrang nets in Tasik Agung village, Rembang Regency. The purpose in this research is to know the local wisdom in Utilizing cantrang nets and the impact of banning the use of cantrang nets. This research uses qualitative method. The result of this research in analized by using determinisme theory from Julian Steawerd and concept of adaptation and environment form Kaplan. The result of this study indicate that the cultural system and local knowledge in the community Tasik Agung village is a prcess of understanding the environtment. And the prohibition of the use of nets cantrang overall impact not only the fisherman who feel but the wider community also impact.